Organic Structure Determination Using 2-D NMR Spectroscopy : a Problem-Based Approach. - Simpson, Jeffrey H. (Elsevier Science, 2012)
This book contains 30-40 quality 2D NMR data sets following an introductory section describing the methodology employed. Many other books describe the methods used, but none offer a large number of problems. Instructors at universities and colleges at the present time are forced to cobble together problems from a wide range of sources. The fragmentary approach to assembling course materials has a negative impact on course continuity and thus adversely impacts student retention. This book will stand as a single source to which instructors and students can go to obtain a comprehensive compe.